Cor pulmonale and silicosis: a necropsy based case-control study. Issue 6 (June 1993) - Murray, J; Reid, G; Kielkowski, D; de Beer, M
Abstract : The presence of cor pulmonale at death in relation to other factors such as emphysema, silicosis, and thromboembolism was analysed in a case-control study of 732 South African gold miners. Marked emphysema was the highest risk factor with an odds ratio of 21.32 (95% confidence interval (95% CI) 5.02-90.7), then extensive silicosis (OR 4.95, 95% CI 2.92-8.38) and thromboembolic disease (OR 1.92, 95% CI 1.37-2.69). Age and smoking were not significant predictors of cor pulmonale.